Analysis of citizen satisfaction in municipal services - José Fernando Romero-Subia; Juan Antonio Jimber del Río; María Salomé Ochoa-Rico; Arnaldo Vergara-Romero (Economies, 2022)
Citizen demand for quality public services is increasing, and improvements in the provision of public services affect citizen satisfaction and loyalty. This research is to evaluate citizens' loyalty to municipal officials on the quality of public services provided by the municipality. The measurement is made through a household-level survey, with a sample of 428 valid questionnaires, in a rural parish of Tengel in Guayaquil, following the American Customer Satisfaction Index (ACSI). This study used the Warp-PLS 7.0 software with a structural equation model to evaluate the seven hypotheses raised. A new component is included in this research: the effect of perceived quality in the provision of municipal services in rural areas on the value ratio perceived by the citizen and overall satisfaction. The results obtained allowed us to observe that the loyalty of the citizen to the elected municipal officials depends on citizen satisfaction with the public services provided by the municipal administration in rural areas. In addition, the quality perceived by the citizen modulates at different levels the relationships between the perceived value and the citizen satisfaction. Areas of improvement in the provision of public services such as municipal police, firefighters, veterinary services, parking services and address information were identified. The findings would allow local public administrators to take action to improve the services provided in rural areas in order to maintain the loyalty of citizens.
Keywords: 330; SEM; ACSI; citizen satisfaction; municipal services; rurality